Mental health of women who suffer intimate partner violence during pregnancy - Mariana de Oliveira Fonseca-Machado; Lisiane Camargo Alves; Patrícia Scotini Freitas; Juliana Cristina dos Santos Monteiro; Flávia Gomes-Sponholz (Universidad de Antioquia, 2014)
Objective. To identify the relationship between intimate partner violence (IPV) during pregnancy and mental disorders in women in the pregnancy-puerperal cycle. Methodology. A review was conducted of papers published in Portuguese, English and Spanish regarding the study theme. The databases explored were PubMed, CINAHL, LILACS and PsycINFO. Results. The 17 included papers studied the relationship between IPV and: pre- and postpartum depression (41%); pregnancy anxiety (23%) and pregnancy posttraumatic stress disorder (12%). None of the studies investigated the association between IPV and suicidal ideation. Conclusion. IPV against women during the pregnancy-puerperal cycle causes negative impacts on mental health. Concrete actions shall be proposed regarding the prevention, identification and treatment of women exposed to IPV during their pregnancy period.